Evaluation of Bioactive Compounds and Antimicrobial Analysis of the Essential Oil From the Leaves of Sauropus androgynous in Rajasthan India - John, Alagbe, Olujimi (American Journal of Biology and Natural Sciences, 2026)
Sauropus androgynous essential oil contains unique bioactive compounds with therapeutic potentials and it delivers powerful antioxidant, anti-inflammatory, antidiabetic, cytotoxic, gastro-protective, immune-protective, cardio-protective, antimicrobial, antidiarrheal, anti-helminthic amongst others. GC-MS analysis of Sauropus androgynous essential oil revealed the presence of 33 bioactive compounds were recorded representing 96.27 % composition dominated by Squalene (19.63 %), Caryophyllene (13.92 %), Nonane, 4-methyl (13.82 %) and n-hexadecanoic acid (10.45 %). Other bioactive compounds examined had a concentration less than 3 %. A synergy between the major and minor compounds are working together to protect, heal, restore and improve the overall vitality of the body. The result obtained on the antimicrobial activity of Sauropus androgynous essential oil revealed a high percentage inhibition 77.81 % , 72.00 %, 80.09 %, 73.73 % and 76.26 % against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Shigella flexineri and Salmonella typhi respectively. The results compare well with that of the standard drug (Ciproflaxacin) (65.00 -71.00 %). It was concluded that Sauropus androgynous essential oil contains measurable concentration of compounds that can disrupt the cell membrane of pathogens and will also help to address the increasing cases of antimicrobial resistance.